The competitive advantage and the growth of Takaful Ikhlas Sdn Bhd products / Mohd Hasbullah Halmi - Halmi, Mohd Hasbullah (Faculty of Business and Management, 2011)
The purpose of this research is to study the competitive advantage and the growth of Takaful Ikhlas Sdn Bhd products. The research is exploratory research. In this study also researcher make an assumptions that with IKHLAS products has been successful in market, Takaful IKHLAS will make more profit regarding to the premium and also can bear a losses towards claims. Researcher also tries to include and find recommendation guideline in promoting IKHLAS products. In this study, the methods used are observation, interview and questionnaire to identify the relevant information regarding the study. Researcher used secondary data such as journal, articles, newspaper, magazines, report as well as primary data. All the data obtained from TISB that runs through July 2003 until 2009. The researcher also structured questionnaire design to obtain the information. Researcher also used probability sampling technique which is the simple random sampling to gain information regarding this research. 30 questionnaires were given to respondents to answer the questionnaire. The result on the competitive advantage and the growth of Takaful Ikhlas Sdn Bhd product may need changes or improvement in their performance in order to able in providing good quality of products and give competitive advantages to other companies.